Métodos eletroanalíticos para detecção de ivermectina em meio aquoso - FERREIRA, Dianderson Cristiano Monteiro (2024)
During the COVID-19 pandemic, in the period from March 2020 to May 2023, caused by the novel coronavirus SARS-CoV-2, various medications were prescribed for the treatment and early prevention of symptoms associated with this disease. Ivermectin (IVM), being a broad-spectrum antiparasitic drug, was one of these medications, although its use has not demonstrated proven efficacy in combating this disease. Composed of two avermectins, which are toxic to humans at high doses, the unregulated use of ivermectin has become a growing concern, necessitating means for its determination and drawing the attention of the academic community. Among the methods being explored, electrochemical methods have gained considerable prominence due to their high sensitivity, rapid response, and simplicity in analyses. In this study, electrochemical sensors based on laser-induced graphene were developed, as well as a glassy carbon electrode modified with Super-P carbon black (CBSP/GCE) (1 mg L−1 in dimethylformamide) for the determination of ivermectin. Using differential pulse voltammetry (DPV) technique, and following optimization of the parameters, the laser-induced graphene electrode exhibited a linear working range of 10−100 (μmol L−1), a limit of detection (LOD) of 1.6 (μmol L−1), a limit of quantification (LOQ) of 4.8 (μmol L−1), and a sensitivity of 7.08 × 10−3 (μA μmol−1 L mm−2). The developed method was successfully applied to water samples (94% recovery), urine samples (113% and 97% recovery), and pharmaceutical samples (approximately 6.0 mg/tablet as indicated on the labels), with analyses performed in triplicate. For the CBSP/GCE electrode, the DPV technique was also utilized, and after optimization, a linear working range of 10−100 (μmol L−1) was achieved, with LOD and LOQ of 1.3 and 4.2 (μmol L−1), respectively, and a sensitivity of 7.45 × 10−3 (μA μmol−1 L mm−2). The method was successfully applied to water samples (100% and 105% recovery), a urine sample (108% recovery), and pharmaceutical samples (approximately 6.0 mg/tablet as indicated on the labels), with analyses performed in triplicate. These results demonstrate the feasibility of the method for routine analyses involving different samples.